Sorceress - Gray, Claudia (Gray, Claudia. Spellcaster novel., 2016)
Nadia, in order to save her family, friends, and her love, Mateo, swears her allegiance to the One Beneath and to learning dark magic. Secretly she searches for a way to defeat the One Beneath, but the temptation of the magic power may be too much for her. Meanwhile, the unlikely love of demon Asa for Verlaine may prove the salvation of them all.